The stories about Montoneros, between conservative revisionism and intellectual progressism - Campos, Esteban (Universidad Nacional del Litoral, 2021)
The purpose of this paper is to reflect on the historical narratives of popularization that have the Montoneros guerrilla as an object. The selection includes the books Operación Primicia, by Ceferino Reato (Sudamericana, 2010), Montoneros. Soldados de Peron, ¿Soldados de Massera? by Carlos Manfroni (Sudamericana, 2012), and Peron y la Triple A. Las 20 advertencias a Montoneros, by Sergio Bufano (Sudamericana, 2015). The paper contextualizes the works in the transition from the memory regime of the Kirchnerist governments to a struggle between narratives of the recent past marked by conservative revisionism, which generated the conditions for the irruption of the negationist discourse. Secondly, the text proposes to reconstruct the nuclei of meaning about Argentina in the 1970s, with the aim of reflecting on the production of historical common sense around Montoneros.